Delik Santet Dalam Konstruksi Rancangan Kitab Undang-Undang Hukum Pidana - Satriadi satriadi (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
This study discusses witchcraft (santet) as one of the controversial offenses in the Criminal Code Bill. Socially, witchcraft (santet) is believed to be an act that can harm people, narrate, or even kill people. However, based on the principle of legality and the difficulty of proving, acts of witchcraft (santet) cannot be criminalized so it is not uncommon for people accused of being witchcraft (santet) to due of process of law. To analyze and understand the offense of witchcraft (santet) in the construction of the Draft Bill of the Criminal Code, this study utilizes normative legal research methods whose data are obtained through a literature study. The results showed that witchcraft (santet) as a criminal act was constructed into the category of the formal offense whose proof did not lead to the presence or absence of magical power possessed by someone, but criminalized was a criminal offense committed, namely a person who intentionally announced he had supernatural powers, offered his services in undertaking harm to others in the form of illness, death or mental or physical suffering.